login
This site is supported by donations to The OEIS Foundation.

 

Logo

Annual Appeal: Please make a donation (tax deductible in USA) to keep the OEIS running. Over 5000 articles have referenced us, often saying "we discovered this result with the help of the OEIS".

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A132148 Triangular array T(n,k) = C(n,k)*Lucas(n-k), 0 <= k <= n. 3
2, 1, 2, 3, 2, 2, 4, 9, 3, 2, 7, 16, 18, 4, 2, 11, 35, 40, 30, 5, 2, 18, 66, 105, 80, 45, 6, 2, 29, 126, 231, 245, 140, 63, 7, 2, 47, 232, 504, 616, 490, 224, 84, 8, 2, 76, 423, 1044, 1512, 1386, 882, 336, 108, 9, 2, 123, 760, 2115, 3480, 3780, 2772, 1470, 480, 135, 10, 2 (list; table; graph; refs; listen; history; text; internal format)
OFFSET

0,1

LINKS

Table of n, a(n) for n=0..65.

FORMULA

G.f.: (2 - (2x + 1)*t)/(1 - (2x + 1)*t + (x^2 + x - 1)*t^2) = 2 + (1 + 2*x)*t + (3 + 2*x + 2*x^2)*t^2 + (4 + 9*x + 3*x^2 + 2*x^3)*t^3 + ... .

The row polynomials L(n,x) = Sum_{k = 0..n} C(n,k)*Lucas(n-k)*x^k satisfy L(n,x)*F(n,x) = F(2*n,x), where F(n,x) = Sum_{k = 0..n} C(n,k)*Fibonacci(n-k)*x^k.

Other identities and formulas include:

L(n+1,x)^2 - L(n,x)*L(n+2,x) = -5*(x^2 + x - 1)^n;

L(n+1,x) - (x^2 + x - 1)*L(n-1,x) = 5*F(n,x) for n >= 1;

L(2*n,x) - 2*(x^2 + x - 1)^n = 5*F(n,x)^2;

L(n,2*x) = Sum_{ k = 0..n} C(n,k)*L(n-k,x)*x^k;

L(n,3*x) = Sum_{ k = 0..n} C(n,k)*L(n-k,2x)*x^k etc.

Sum_{k = 0..n} C(n,k)*L(k,x)*F(n-k,x) = 2^n*F(n,x).

Row sums: L(n,1) = Lucas(2*n); Alternating row sums: L(n,-1) = (-1)^n*Lucas(n); L(n,1/phi) = (-1)^n*L(n,-phi) = sqrt(5)^n for n >= 1, where phi = (1 + sqrt(5))/2.

The polynomials L(n,-x) satisfy a Riemann hypothesis: the zeros of L(n,-x) lie on the vertical line Re x = 1/2 in the complex plane.

From Peter Bala, Jun 29 2016:

L(n,x) = (x + phi)^n + (x - 1/phi)^n, where phi = (1 + sqrt(5))/2. The zeros of L(n,x) are given by -1/2 - i*sqrt(5)/2*cot( (2*k - 1)*Pi/(2*n) ) for k = 1..n.

d/dx(L(n,x)) = n*L(n-1,x).

L(-n,x) = L(n,x)/(x^2 + x - 1)^n.

L(n,x - 1) = (-1)^n*L(n,-x).

L(n,x)^2 - L(2*n,x) = 2*(x^2 + x - 1)^n.

L(n,x)^3 - L(3*n,x) = 3*(x^2 + x - 1)^n*L(n,x).

L(n,x)^4 - L(4*n,x) = 4*(x^2 + x - 1)^n*L(n,x)^2 - 2*(x^2 + x - 1)^(2*n).

If n divides m and m/n is odd then L(n,x) divides L(m,x) in the polynomial ring Z[x].

L(n,x) = F(n+1,x) - (x^2 + x - 1)*F(n-1,x) = 2*F(n+1,x) - (2*x + 1)F(n,x), where F(n,x) = Sum_{k = 0..n} binomial(n,k)*Fibonacci(n-k)*x^k denotes the row polynomials of A094440 (taken with an offset of 0).

exp( Sum_{n >= 1} L(n,x)*z^n/n ) = Sum_{n >= 0} F(n+1,x)*z^n.

exp( Sum_{n >= 1} L(n,x)*L(2*n,x)*z^n/n ) = 1/( F(1,x)*F(2*x)*F(3,x) ) * Sum_{n >= 0} F(n+1,x)*F(n+2,x)* F(n+3,x)*z^n. (End)

EXAMPLE

Triangle starts

2;

1, 2;

3, 2, 2;

4, 9, 3, 2;

MAPLE

with(combinat): lucas := n -> fibonacci(n-1) + fibonacci(n+1): T := (n, k) -> binomial(n, k)*lucas(n-k): for n from 0 to 10 do seq( T(n, k), k = 0..n) od;

MATHEMATICA

Flatten[Table[Binomial[n, k]LucasL[n-k], {n, 0, 10}, {k, 0, n}]] (* Harvey P. Dale, Nov 06 2011 *)

CROSSREFS

Cf. A000032 (T(n,0)), A000045, A005248 (row sums), A061084 (alter. row sums), A094440.

Sequence in context: A111725 A112218 A172366 * A237829 A159974 A143866

Adjacent sequences:  A132145 A132146 A132147 * A132149 A132150 A132151

KEYWORD

easy,nonn,tabl

AUTHOR

Peter Bala, Aug 17 2007

STATUS

approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent | More pages
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy .

Last modified December 8 22:51 EST 2016. Contains 278957 sequences.